2022
DOI: 10.1038/s41419-022-05417-0
|View full text |Cite
|
Sign up to set email alerts
|

PSMA1 mediates tumor progression and poor prognosis of gastric carcinoma by deubiquitinating and stabilizing TAZ

Abstract: The deubiquitinating enzyme family in tumor progression play important role in intracellular protein degradation. The proteasome subunit alpha type 1 (PSMA1) has been reported to act as an oncogene in several human cancers. The present study aimed to reveal the functional significance of PSMA1 in gastric cancer (GC) progression and the underlying mechanisms. The expression of PSMA1 in human GC samples and GC cell lines was examined by western blot analysis, real-time PCR, immunohistochemistry (IHC), and in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…The cell lysates were incubated overnight with Protein-A/G MagBeads (Yeasen, Shanghai, China) and anti-ELAVL1 antibody (Cell Signaling Technology) or normal rabbit IgG (Cell Signaling Technology) at 4 °C. The protein complexes were retrieved, washed, and subjected to western blotting with an anti-ubiquitin antibody (Cell Signaling Technology) [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The cell lysates were incubated overnight with Protein-A/G MagBeads (Yeasen, Shanghai, China) and anti-ELAVL1 antibody (Cell Signaling Technology) or normal rabbit IgG (Cell Signaling Technology) at 4 °C. The protein complexes were retrieved, washed, and subjected to western blotting with an anti-ubiquitin antibody (Cell Signaling Technology) [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported alterations in the expression of single proteasome subunits in various types of cancer. PSMA1, a subunit of the 20S CP, has been found to be overexpressed and considered a prognostic or cancer marker in several tumors, including lung, gastric, breast and colon cancer [15][16][17][18]. Indeed, proteasome α-subunits have been associated with the development and progression of several types of cancers, including hepatocellular carcinoma, breast cancer, lung cancer, and multiple myeloma [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%